Use of Electronic School Books (BSE) as a Resource Learning in the Historical Social Studies Learning Process in SMP Negeri 1 Batang - Nurmanuel, Pratiwi Chrisnanda (Indonesian Journal of History Education, 2017)
This study aims to determine the understanding and use of BSE in social studies learning history and the effective use of Electronic School Books as a learning resource in SMP Negeri 1 Batang. This research is qualitative. Informants in this study were social studies teachers, students, principals, BOS treasurer, and librarian. The data was obtained through interviews, observation, and documentation. This research focuses on understanding how teachers and students use BSE and its effectiveness. The selection technique for informants in this study is purposive sampling. The results use BSE as a learning resource in the history of social studies learning has not been effectively implemented due to a lack of understanding of teachers and students regarding BSE and the lack of utilization of school facilities to support the implementation of electronic learning systems, especially BSE.